Hyperbaric oxygen treatment increases intestinal stem cell proliferation through the mTORC1/S6K1 signaling pathway in Mus musculus - Ignacio Casanova-Maldonado; David Arancibia; Pablo Lois; Isaac Peña-Villalobos; Verónica Palma (Biological Research, 2023)
Abstract Background Hyperbaric oxygen treatment (HBOT) has been reported to modulate the proliferation of neural and mesenchymal stem cell populations, but the molecular mechanisms underlying these effects are not completely understood. In this study, we aimed to assess HBOT somatic stem cell modulation by evaluating the role of the mTOR complex 1 (mTORC1), a key regulator of cell metabolism whose activity is modified depending on oxygen levels, as a potential mediator of HBOT in murine intestinal stem cells (ISCs). Results We discovered that acute HBOT synchronously increases the proliferation of ISCs without affecting the animal’s oxidative metabolism through activation of the mTORC1/S6K1 axis. mTORC1 inhibition by rapamycin administration for 20 days also increases ISCs proliferation, generating a paradoxical response in mice intestines, and has been proposed to mimic a partial starvation state. Interestingly, the combination of HBOT and rapamycin does not have a synergic effect, possibly due to their differential impact on the mTORC1/S6K1 axis. Conclusions HBOT can induce an increase in ISCs proliferation along with other cell populations within the crypt through mTORC1/S6K1 modulation without altering the oxidative metabolism of the animal’s small intestine. These results shed light on the molecular mechanisms underlying HBOT therapeutic action, laying the groundwork for future studies.